Fourier Transform Infrared Spectroscopy Applied to the Study of Unicellular Models - Magalhaes, Sandra; Nunes, Alexandra (Current Metabolomics, 2018)
Background: Vibrational spectroscopy has shown the capacity to provide rapid, accurate and relevant information on microorganism's classification and identification. In fact Fourier Transform Infrared Spectroscopy is a sensitive and effective methodology in food analysis, clinical diagnosis and environmental evaluation, with successful identification at genus and species level. Focus: The interest in this technique lies not only in the identification and classification of bacteria, but there is also relevance in using FTIR to follow cellular responses to stress in unicellular models, with particular interest in yeasts and so far results show FTIR is able to evaluate specific cellular changes related to stress stimulus, mainly in protein region. Prospect: This work gathered information that demonstrates that it is possible to overcome signal overlapping and use Fourier Transform Infrared Spectroscopy and multivariate analysis tools to obtain biochemical signatures of microorganisms and corresponding metabolome that can provide inexpensive and highly specific alternatives to conventional typing methods. Also, it presents a spectrum representative of a microbial cell and summarizes in a table the spectral assignments of main biological contributors.
Keywords: microbial identification